Doses de fósforo na produção das mudas e sua influência na produção e qualidade de tomate - Martins, Bruno Novaes Menezes [UNESP] (2015)
Considering the lack of studies related to phosphorus application in the production of tomato seedlings and its effect after transplantation to the harvesting stage, the aim of this study was to evaluate the effects of doses of phosphorus supplied by fertigation to the sown seedlings in coconut fiber base substrate, production and quality of tomato fruits. The experiment was conducted from August 2013 to January 2014 in São Manuel Experimental Farm, located in São Manuel, SP. The experimental design was used in a randomized complete block design with four replications. We evaluate six treatments (P doses): 0; 15; 30; 45; 60 and 75 mg of P L-1, using monoammonium phosphate (MAP of 10.5% of P and 9% of N,) as source of P and N. On the day of transplanting, it was evaluated: leaf area (cm2); seedling height (cm), stem diameter, seedling (mm), fresh weight of shoot and root (g planta-1), dry matter of shoots and roots (g planta-1). It wasalso evaluated plant production (kg), productivity (t ha-1), number of fruits per plant, diameter and height of fruit (mm), average weight per fruit (g fruit-1) and early production. It was evaluated physical and chemical characteristics of fruits in four crops: pH, titratable acidity, Soluble solids, reducing sugars, ascorbic acid, maturation index (Ratio), chlorophyll a and b, lycopene and β-carotene. The results support the conclusion that tomato seedlings grown on substrates coconut fiber containing phosphorus, respond to the increase in phosphorus supply with an increase in leaf area, seedling height, fresh weight of the area part and roots. However, the increases in vegetative characteristics of tomato seedlings provided by increase in phosphorus level did not favor increased productivity and fruit mass. Regarding the fruit's physical and chemical characteristics, the best quality seedling tomato favored due to the increase in phosphorus levels did not affect ...